[Re]-appearances online: photography, mourning and new media ecologies for representing the Southern Cone's disappeared on two digital memory platforms. (2nd September 2022) - Bustamante-Brauning, Sebastian
Abstract : The practice of enforced disappearances fundamentally alters memorialisation rituals as relatives do not have a body to localise mourning as is possible with processes of death. Families in the Southern Cone of South America (Chile/Argentina) have sought new ways to remember the dictatorship missing who remain in a liminal space between life and death. As a vehicle to represent public grief, photography became vital; families marched with photographs of their disappeared relatives on placards or pinned to their chests. Studies on the importance of photography and disappearance have come some way in elucidating the photographic medium's unique role of in representing the disappeared. However, little scholarship has looked at the role of photography and new media in these histories. Charting the use of photographs in Chile and Argentina to represent the disappeared and their families' grief, this article engages with their suspended mourning drawing on content and visual analysis alongside expert interview data. By analysing two websites that reproduce photographs of the disappeared: www.memoriaviva.com and www.recordatorios.com.ar, the article looks at the use of photography in the digital ecology. Both sites show photography's continued importance for rituals of remembrance and to demand accountability in the present and for the future.